2022
DOI: 10.1038/s41467-022-28588-y
|View full text |Cite
|
Sign up to set email alerts
|

RIF1-ASF1-mediated high-order chromatin structure safeguards genome integrity

Abstract: The 53BP1-RIF1 pathway antagonizes resection of DNA broken ends and confers PARP inhibitor sensitivity on BRCA1-mutated tumors. However, it is unclear how this pathway suppresses initiation of resection. Here, we identify ASF1 as a partner of RIF1 via an interacting manner similar to its interactions with histone chaperones CAF-1 and HIRA. ASF1 is recruited to distal chromatin flanking DNA breaks by 53BP1-RIF1 and promotes non-homologous end joining (NHEJ) using its histone chaperone activity. Epistasis analys… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 92 publications
(181 reference statements)
0
10
0
Order By: Relevance
“…Meanwhile, the HIRA complex associates with both ASF1 isoforms, consistent with our network analysis ( Figure 1 B) and a recent study. 67 …”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, the HIRA complex associates with both ASF1 isoforms, consistent with our network analysis ( Figure 1 B) and a recent study. 67 …”
Section: Resultsmentioning
confidence: 99%
“…During homologous recombination, PCNA is loaded on the strand invaded D-loop and we speculate that this could result in the recruitment of TLK1 and TLK2 there for the regulation of repair factors at damaged chromatin, including RAD54 and ASF1 (34, 39, 61, 62). In line with a recent study, the hypersensitivity of TLK depletion implicates their potential involvement in homologous recombination repair(1).…”
Section: Discussionmentioning
confidence: 99%
“…How could successful repair of a DSB lesion lead to lasting topological changes? It has been shown that chromatin around a DSB undergoes a massive 3-D restructuring converging on transcriptionally silent domains that are, at least in part, defined by adjacent TAD boundaries and whose spatial arrangement related to the neighbouring TADs is stabilized by dedicated factors including the cohesin complex, 53BP1, RIF1 and SLFN5 genome caretakers, or ASF1 histone chaperone ( 24 , 28 , 30 , 31 , 63 ). These previous studies showed that DNA repair process per se can benefit from such chromatin restructuring (e.g.…”
Section: Discussionmentioning
confidence: 99%